Comparing the scaffolding provided by physical and virtual manipulative for students' understanding of simple machines - Chini, Jacquelyn J. (Kansas State University, 2010)
Conventional wisdom has long advised that students’ learning is best supported by interaction with physical manipulative. Thus, in the physics laboratory, students typically spend their time conducting experiments with physical equipment. However, computer simulations offer a tempting alternative to traditional physical experiments. In a virtual experiment, using a computer simulation, students can gather data quickly, and measurement errors and frictional effects can be explicitly controlled. This research investigates the relative support for students’ learning offered by physical and virtual experimentation in the context of simple machines. Specifically, I have investigated students’ learning as supported by experimentation with physical and virtual manipulative from three different angles-- what do students learn, how do students learn, and what do students think about their learning. The results indicate that the virtual manipulative better supported students’ understanding of work and potential energy than the physical manipulative did. Specifically, in responding to data analysis questions, students who used the virtual manipulative before the physical manipulative were more likely to describe work as constant across different lengths of frictionless inclined planes (or pulley systems) and were more likely to adequately compare work and potential energy, whereas students who used the physical manipulative first were more likely to talk about work and potential energy separately. On the other hand, no strong support was found to indicate that the physical manipulative better supported students’ understanding of a specific concept. In addition, students’ responses to the survey questions indicate that students tend to value data from a computer simulation more than from a physical experiment. The interview analysis indicates that the virtual environment better supported the students to create new ideas than the physical environment did. These results suggest that the traditional wisdom that students learn best from physical experiments is not necessarily true. Thus, researchers should continue to investigate how to best interweave students’ experiences with physical and virtual manipulatives. In addition, it may be useful for curriculum designers and instructors to spend more of their efforts designing learning experiences that make use of virtual manipulatives.
Keywords: Physics education research; Student understanding; Simulation; Traditional laboratory; Simple machines; Education, Sciences (0714); Physics, General (0605)